Evaluation of residual stress and adhesion of Ti and TiN PVD films by laser spallation technique. (August 2018) - Radziejewska, J.; Sarzyński, A.; Strzelec, M.; Diduszko, R.; Hoffman, J.
Highlights: LST provides means for examination of properties of technological films. Residual stresses in films with texture or week crystallization can be determined. LST method can be applied for technological films with good adhesion. No rapid debonding of films was stated. Reflected waves should be taken into account in determining an interface strength. Abstract: The laser spallation technique was applied for measurement of residual stress and adhesion of thin films. Two films of different properties, ductile and soft Ti, and hard and brittle TiN, were studied. The films were produced on 304 steel substrate by PVD method. The residual stress value obtained by laser spallation technique LST were compared with stress value from X-ray diffraction method. Good agreement of stress values measured by both methods was attained. Additionally, the interface strength of the films was tested by laser adhesion spallation technique LASAT with use of VISAR system. It was shown that shock wave induced by a nanosecond laser pulse adequately determines properties of PVD thin films on metal substrate.